The Acceptance of Students with Physical Disabilities by Their Peers in Inclusive and Non-Inclusive Schools in Tehran - Narges Adib-Sereshki; Yeganeh Saleh-Pour (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: The present research determines the level of peer acceptance of students with physical disabilities in inclusive and non-inclusive schools. A number of studies which have sought to identify the influential factors in the success of inclusive education, have pointed out the acceptance of special need student by his/her regular peers to be a significant variable. Materials & Methods: This is a descriptive investigation. The instrument utilized was the Acceptance Scale (Voelts, 1980). The upper elementary level version that we were used consists of 34 items, two are general friendship items, two are veridicalite items, and the remaining items are acceptance items.Three response options are provided for each item,I agree, I disagree, and maybe. For such reliability, a Spearman-Brown corrected split-half reliability index of +.82 was reported, as well as an alpha coefficient of +.77. A test -retest stability coefficient of .68 was obtained by retesting a sample of 101 children on two occasions separated by three weeks. In Iran, with test retest on 72 students we got Reliability coefficient of .83. The sample includes 179 student boys and girls in grades three to five who had classmates with physical disability in their elementary schools in Tehran. This sample was randomly selected from each of the five different regions in the city of Tehran. In addition, for the purpose of comparison, a sample of fifty-five students in similar grades was studied in regular schools. The effect of gender and type of school (inclusive vs. non-inclusive) on students' acceptance of a peer with physical disability all were assessed. Results: Results indicated that acceptance level is similar in boys and in girls in inclusive schools. The girl and boy students in inclusive schools demonstrated a significantly higher level of peer acceptance than their pupils in non-inclusive schools. This difference was much more noticeable in boy students. The lowest level of acceptance was found in the group of boy students in non-inclusive schools. Conclusion: As the results indicate, students with physical disabilities are much highly accepted by their peers in inclusive schools as compared with those in regular schools. This greater level of acceptance in inclusive schools could be reflective of the reality that the experience of contact and familiarity with a child who has a special need may encourage his/her feeling of being accepted by regular students. The limitations of this investigation and the overall scarcity of research in this area (in our country) points out more needs for further researches, specially in regard to appropriate interventions for enhancement of peer acceptance.